DINAMIKA DISKUSI INVESTASI GENERASI Z DI MEDIA SOSIAL : ANALISIS BEHAVIORAL FINANCE - JUM'AN (Cross-Border Journal of Business Management, 2026)
The rapid growth of social media has significantly transformed how Generation Z acquires financial information and makes investment decisions. As digital natives, Generation Z actively engages in online discussions through platforms such as Instagram, TikTok, Telegram, and Discord, where investment narratives, trends, and opinions circulate rapidly. From a behavioral finance perspective, investment decisions are not purely rational but are often influenced by psychological biases emerging from social interaction and digital communication dynamics. However, limited qualitative research explores how these online discussions shape behavioral biases and investment decision-making among Generation Z. This study aims to analyze the dynamics of investment discussions among Generation Z on social media and to identify behavioral finance biases embedded in these digital interactions. Specifically, it seeks to explore how online discourse contributes to the formation of risk perception, return expectations, and final investment choices. This research employs a qualitative approach using digital ethnography. Data were collected through in-depth semi-structured interviews with 18 Generation Z investors aged 18–26 years who actively participate in online investment communities. Additionally, participatory observation was conducted in selected Telegram and Discord investment groups, as well as content analysis of investment-related discussions on TikTok and Instagram. The data were analyzed using thematic analysis involving open, axial, and selective coding to identify recurring patterns and behavioral constructs. The findings reveal that social media discussions play a central role in amplifying herding behavior, Fear of Missing Out (FOMO), overconfidence, and confirmation bias among Generation Z investors. Investment decisions are frequently influenced by viral narratives, influencer opinions, and peer validation rather than comprehensive fundamental analysis. The study also identifies a cyclical mechanism in which digital interaction reinforces collective sentiment, which subsequently shapes individual risk-taking behavior. These results contribute to the development of a conceptual model linking digital social interaction, behavioral biases, and investment decision-making among Generation Z, offering implications for digital financial literacy policies and investor education strategies.